A comparison of mammography and ultrasonography in the evaluation of breast masses - Prasad, Sachin N.; Houserkova, Dana (Biomedical papers, 2007)
Aim: Aim of the study is to evaluate breast masses using mammography (MG) and ultrasonography (USG) independently and in combination.Materials and methods: Our study group consisted of 62 female patients, with breast symptoms such as palpable lumps, pain in the breast and nipple discharge who were examined prospectively over a period of 6 months. All 62 patients were examined by both MG and USG independently. Fine needle aspiration cytology (FNAC) or core cut biopsy was done according to the findings of MG and USG and then the results were correlated with each modality finding.Results: According to this study MG showed an efficiency of 81.8 % compared to 95.5 % for USG in detecting fibrocystic mastitis. However their combined approach resulted in 100 %. In the case of fibroadenomas, MG showed 75 % efficiency and USG only 35 % and the combination resulting in 93.7 %. For carcinomas, MG had an efficiency of 77.8 % and USG 55.6 %, but the combination had an efficiency of 98.1 %. Overall, the histopathological results when correlated with each modality finding showed that MG had an efficiency of only 77.4 % and USG only 69.8 % when used alone in detecting these lesions of the breast compared to an efficiency of 98.1 % obtained by their combined approach. In our study, we showed that there was no significant difference in sensitivity between MG and USG (p = 0.3768) but there was significant difference in MG alone and MG-USG combination (p = 0.0015) and USG alone and USG-MG combination (p = 0.0001).Conclusion: Our study confirmed that combined MG and USG had higher sensitivity rate than the sensitivity rate observed for either single modality. The diagnostic accuracy for carcinomas of the breast appear to improve when MG was combined with USG, even in cases which showed no evidence of microcalcification or other signs of abnormalities. Our study implies that, USG may be the only viable modality in pregnant and lactating women as it does not involve ionizing radiation and also in dense breast tissue, as density is a limiting factor for MG.
Keywords: Keywords: Mammography/Ultrasonography/Breast masses/FNAC/Breast cancer